Prison misconduct among female inmates with mental disorders, substance abuse/dependence, and co-occurring disorders in Taiwan. Issue 3 (3rd July 2019) - Kuo, Shih-Ya; Zhao, Ruohui
ABSTRACT: This survey study attempted to address two research questions: (1) whether female inmates with either singular mental illness or singular substance abuse/dependence disorders were more likely to break institutional rules in prison than their disorder-free counterparts; and (2) whether female inmates with both mental illness and substance abuse/dependence disorders (CODs) were more likely to engage in misbehaviour than either disorder-free or singularly disordered women during the course of their confinement. The current study employed a sample of 643 female inmates and the data for analyses contained information on inmates' CODs, mental and substance abuse/dependence disorders, and pre-prison and prison experiences. The results showed that female inmates with CODs committed the most misconduct in prisons, but no significant effect was found on prison misconduct among inmates with singular disorders and disorder-free female inmates. Possible explanations for these results were suggested, and public policy implications were discussed in the concluding section.